2016
DOI: 10.1093/cid/ciw546
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis-Associated Pneumonia in Infants and Children From Low- and Middle-Income Countries Participating in the PERCH Study

Abstract: Background. Few data exist describing pertussis epidemiology among infants and children in low- and middle-income countries to guide preventive strategies.Methods. Children 1–59 months of age hospitalized with World Health Organization–defined severe or very severe pneumonia in 7 African and Asian countries and similarly aged community controls were enrolled in the Pneumonia Etiology Research for Child Health study. They underwent a standardized clinical evaluation and provided nasopharyngeal and oropharyngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…In this study, we detected Bordetella pertussis in 5 young children. Identification of Bordetella pertussis in BALF or OPS specimens may provide predictive value for the outcome of respiratory illness at the individual case level [23]. In terms of some pathogens such as influenza A, adenovirus, Mycoplasma pneumoniae and Streptococcus pneumoniae, relatively low concordance between BALF and OPS specimens for them may reflect different cell tropisms for different parts of the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we detected Bordetella pertussis in 5 young children. Identification of Bordetella pertussis in BALF or OPS specimens may provide predictive value for the outcome of respiratory illness at the individual case level [23]. In terms of some pathogens such as influenza A, adenovirus, Mycoplasma pneumoniae and Streptococcus pneumoniae, relatively low concordance between BALF and OPS specimens for them may reflect different cell tropisms for different parts of the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter case-control study of children in hospital for severe or very severe pneumonia, the use of induced sputum samples increased the detection of B pertussis using PCR by 48% compared with the use of a combined nasopharyngeal and oropharyngeal swab. 87 Two South African studies also found an increased yield of B pertussis on PCR with induced sputum, 11 88 although no difference was shown in another hospital based study. 89 Several studies have shown good agreement between PCR testing of induced sputum and nasopharyngeal swabs for viruses; the yield is highest when both sample types are tested.…”
Section: Respiratory Samplesmentioning
confidence: 97%
“…Nine studies containing descriptive epidemiology data from ASEAN countries were identified: two hospital-based studies of children with severe pertussis (Kowalzik et al, 2007;Sadiasa et al, 2017), two hospital-based studies of adults with prolonged cough (Siriyakorn et al, 2016;Koh et al, 2016), two seroepidemiology surveys (Wanlapakorn et al 2016;Son et al 2018), and three studies of multiple etiologies of respiratory illness (Wertheim et al 2015;Barger-Kamate et al 2016;Lau et al 2018) (Table 3). Pertussis disease in ASEAN countries is poorly characterized, partly demonstrated by the fact that only six out of ten countries are represented by these nine studies.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…No pertussis-specific symptoms or vaccine status was reported. The Pneumonia Etiology Research for Child Health Study was a multinational, prospective, hospitalbased and community control study which included Thai infants aged 1-59 months presenting with pneumonia between 2011 and 2014 (Barger-Kamate et al, 2016). None of the 224 pneumonia cases tested positive for pertussis by PCR while three (0.34%) cases (two clinically and one PCR-confirmed case) were found in the control group.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%